Selective load shedding priority algorithm development - Ong, Jing Xian (Nanyang Technological University, 2024)
In modern power systems, load shedding is usually the last resort to maintain system stability. Raising the power generated is the go-to method to tackle increasing load demand. However, when all options are exhausted, load shedding becomes the last resort. A typical power system faces two types of issues. The first issue is under-voltage, where the reactive power absorbed by the grid is too high, which results in grid voltage sag, therefore threatening system failure due to low voltage. The second issue is under-frequency, where the frequency of the grid drops below the rated frequency due to increased active power demand. Both issues can be solved individually by Under-Voltage Load Shedding (UVLS) or Under-Frequency Load Shedding (UFLS), or a combination of both.